Exploring the influence of demographic factors on perceived performance risk among youth towards online shopping in Punjab. (9th July 2019) - Kumar, Pawan; Bajaj, Rakhi
The tremendous growth of internet has accounted for accelerated growth in e tailoring. Online shopping irrespective of its growth marked for small percentage of sale due to perceived risk. The study is designed to examine key components of perceived risk of online shopping among youth of high educational institutes of Punjab. The population consisted of online shoppers of universities of four cities Ludhiana, Jalandhar, Patiala and Amritsar of Punjab. Respondents were selected from different genders, age groups, monthly family income groups and qualifications from these major cities having online shopping experience. A pre structured questionnaire with five point likert rating scale was used to measure these dimensions of perceived risk among online buyers of four cities. Convenience sampling method was used to collect data from sampled respondents. Principal component analysis revealed four key factors of perceived risk in online buying. Performance risk was found as prime component of perceived risk. Influence of demographic factors on perceived performance risk was studied with the help of F ratio showing their relative significance.